The Impact of Transformational Leadership on Employees’ Appraisals of Stressors - Nesdoly, Nina (Université d'Ottawa / University of Ottawa, 2021)
I develop and test a theoretical model to examine how and why transformational leadership affects employees’ appraisals of challenge and hindrance stressors. I draw on the transactional theory of stress to argue that transformational leaders motivate their employees to believe that they can successfully cope with workplace stressors, which in turn encourages them to appraise challenge stressors more positively and hindrance stressors as less threatening. Presenting a parallel mediation model, I test three mediators that operationalize my underlying theory: psychological empowerment; psychological safety; and stress mindsets. I conduct a time-separated online survey study of 255 employed adults. I test my theory through two sets of analyses, considering two sets of dependent variables: (1) appraisals of stressors in general and (2) appraisals of stressors in the context of hypothetical workplace vignettes. My results suggest that (1) transformational leadership was positively associated with challenge appraisals in the context of challenge and hindrance stressors, and negatively associated with hindrance appraisals in the context of challenge and hindrance stressors. Psychological empowerment, but not psychological safety nor stress mindset, was a significant mediator in all cases. (2) Results of the vignette analysis found that transformational leadership was positively associated with challenge appraisals and negatively associated with hindrance appraisals of both challenge and stressor vignettes. However, none of the mediators were significant. I conclude that transformational leaders can help employees appraise stressors more optimistically by empowering them to view themselves as competent and in control in relation to their work. The applications of my research to theory and practice are discussed.
Keywords: Leadership; Stress